Hubungan Antara Persepsi Terhadap Kompensasi Dengan Kepuasan Kerja Karyawan Luwes Gading - Dewani, Fajrina, Drs. Moh. Amir, M.Si., P.Si (2016)
Every employees must have a goal to be achieve, either by job satisfaction by achieve thecompensation. This study aims to (1) determine the relationship between perceptions of compensation and job satisfaction of Luwes Gading employees, (2) determine the effective contribution Job Satisfaction to compensation of Luwes Gading employees, (3) determine the level of perceptions of compensation of Luwes Gading employees, (4) determine the level of job satisfaction of Luwes Gading employees. Research subjects in this study are 80 employees active in Luwes Gading Surakarta, The method used in this research is quantitative method to use 2 scale, the scale of job satisfaction and scale of compensation. Sampling was conducted by random sampling technique on Luwes Gading active employees with the number of 80 people. Data collection tool used to collect data by using the scale of job satisfaction with compensation scale. Data analysis technique used in this study was the statistical technique of Pearson Product Moment. Based on the product moment correlation analysis results showed that there was a positive relationship between perceptions of Highly Significant compensation and job satisfaction of employees in the Luwes Gading, Surakarta.Job Satisfaction variable effective contribution to compensation amounting to 53%, indicated by the correlation (r2) = 0.537. Which means there are 47% of other variables that affect job satisfaction.The level of job satisfaction variables classified in the high category. The level of perceptions of compensation variables classified in the medium category. Keywords : Job Satisfaction, Compensation, Perception of Compensation